Model Matematika Dinamika Sitokin dalam Sistem Respon Inflamasi Akibat Infeksi Penyakit Virus Zoonosis - Sari, Novia Komala; Subhan, Muhammad (Journal of Mathematics UNP, 2024)
Diseases that can be scientifically transmitted between animals and humans are zoonotic diseases. In zoonotic diseases, cytokines act as cell signalers in the body that are useful for understanding immunity to disease infections. This study is a basic or theoretical research by conducting a literature review to understand the interaction between inflammatory pro-response cytokines with inflammatory anti-response. In this study, we will discuss a mathematical model consisting of two simple components, namely pro-inflammatory and anti-inflammatory responses. The analysis used is fixed point analysis. The fixed point obtained is the root of the polynomial to the power of 7 so that the exact value of the fixed point cannot be determined. In finding the fixed point of the system of differential equations used Descartes' rule, so that a positive fixed point of 7, 5, 3 or 1 piece is obtained. We supplemented the results with numerical simulations.